Casting and Forming of Light Alloys - Jiang, Wenming (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to present the latest developments in the casting and forming of light alloys. The preparation process and performance enhancement of Al, Mg or their composite materials are mainly studied. Particular attention has been paid to the relationship between process conditions, microstructural features, and mechanical properties.